Gluten-Free Cookies Innovation Made from Arrowroot Flour (Maranta arundinacea L.) with the Addition of Spinach (Amaranthus sp.) - Musfirotin, Alfina Uli; Khoiriyah, Romyun Alvy; Mustika, Ika (International Conference on Sustainable Health Promotion, 2025)
Cookies are generally high in calories and contain wheat flour, which contains gluten, making them unsuitable for individuals with gluten intolerance. This study developed gluten-free cookies using arrowroot flour (Maranta arundinacea L.) and spinach (Amaranthus sp.) as sources of iron and natural pigments. This study aims to determine the panelists’ acceptance level of cookies made from arrowroot flour with added amaranth. This is an experimental study to evaluate sensory acceptance through a hedonic organoleptic test using a scale of 1–5 for the parameters of appearance, color, aroma, taste, and texture. Thirty untrained panelists aged 19–22 years old were selected to represent general consumers. Appearance received an average score of 4.57; color 4.33; aroma 4.00; taste 3.90; and texture 4.03. These scores indicate that the panelists’ level of liking ranged from like to very like. This product has the potential to be an alternative gluten-free cookie made from local foods enriched with iron..